Overexpression of SmSCR1 Promotes Tanshinone Accumulation and Hairy Root Growth in Salvia miltiorrhiza - Zhou, Wei; Wang, Shuai; Shen, Yafang; Liu, Yunhui; Maoz, Itay; Gao, Xiankui; Chen, Chengan; Liu, Tingyao; Wang, Can; Kai, Guoyin (Frontiers in Plant Science, 2022)
Lipid-soluble tanshinone is one of the main bioactive substances in the medicinal plant Salvia miltiorrhiza, and its medicinal demand is growing rapidly. Yeast extract (YE) modulates the tanshinone biosynthesis, but the underlying regulatory network remains obscure. In the present study, a YE-responsive GRAS transcriptional factor Scarecrow1 (SCR1) was identified in S. miltiorrhiza from the YE-induced transcriptome dataset. SmSCR1 is located in the nucleus. Overexpression of SmSCR1 in S. miltiorrhiza roots resulted in a significantly higher accumulation of tanshinone than the control, with the highest of 1.49-fold increase. We also detected upregulation of tanshinone biosynthetic genes, SmCPS1 and SmHMGR1, and distinct alteration of growth and development of the hairy roots in the overexpression lines compared to the control. An inverse phenotype was observed in SmSCR1-SRDX suppression expression lines. We found that SmSCR1 can bind to the promoter of SmCPS1 to induce its expression. This study provides new insight into the regulatory mechanism on the growth and development of hairy roots, tanshinone accumulation, and the metabolic engineering of bioactive compounds in S. miltiorrhiza.